Reverse transcriptase-polymerase chain reaction for the detection equine rhinitis B viruses and cell culture isolation of the virus - Black, W. D. (Arch Virol, 2006)
Equine rhinitis B virus (ERBV), genus Erbovirus, family Picornaviridae occurs as two serotypes, ERBV1 and ERBV2. An ERBV-specific nested reverse transcriptase-polymerase chain reaction (RT-PCR) that amplified a product within the 3D(pol) and 3′ non-translated region of the viral genome was developed. The RT-PCR detected all 24 available ERBV1 isolates and one available ERBV2 isolate. The limit of detection for the prototype strain ERBV1.1436/71 was 0.1 50% tissue culture infectious doses. The RT-PCR was used to detect viral RNA in six of 17 nasopharyngeal swab samples from horses that had clinical signs of acute febrile respiratory disease but from which ERBV was not initially isolated in cell culture. The sequences of these six ERBV RT-PCR positive samples had 93–96% nucleotide identity with six other partially sequenced ERBV1 isolates and one ERBV2. ERBV was isolated from one of the six samples at fourth cell culture passage when it was shown that the addition of 20 mg/mL MgCl(2) to the cell culture medium enhanced the growth of the virus. This isolated virus was antigenically similar to ERBV2.313/75. Determination of the nucleotide sequence of the P1 region of the genome also indicated that the isolate was ERBV2, and it was therefore designated ERBV2.1576/99. This is the first reported isolation of ERBV in Australia. The study highlights the utility of PCR for the identification of viruses in clinical samples that may initially be considered negative by conventional cell culture isolation.